A assimetria do ato de linguagem no stand-up comedy - Boaventura, Luis Henrique (2013)
This paper thematizes the asymmetry of the speech act in the genre stand-up comedy. The overall goal is to investigate and demonstrate the occurrence of this asymmetry between the processes of production and interpretation in the speech act. The theoretical mark situates in the scope of Semiolinguistics Theory of Discourse, Patrick Charaudeau (2001, 2004, 2008a, 2008b, 2010a, 2010b, 2010c, 2010d, 2012), and Toward a Philosophy of the Act, Mikhail Bakhtin (1997, 2012). Comprise the corpus of this study two jokes written by comedian Rafinha Bastos. In the cases analyzed, the speech act proposed by the comedian failure to receive consideration for their connivance alocutary (the public institution receiving) due to the asymmetry between the processes of production and reception of the speech. The methodological procedures, through a descriptive, qualitative and bibliographic research, clarify the mechanics that governs the basic dynamics of a joke in stand-up comedy genre, or an speech act proposed by the comedian (I) and which he hopes the public (YOU) respond to with the laughter. Held a layout in levels: case presentation, literariness, communication contract (external data and internal data), the world semiotization (transformation process, transaction and interpretation), speech project (the organizational and discursive strategies of speech) and asymmetry of the speech act, culminating in the transfer effects of the internal circuit to the external circuit of this act. The study reveals that the cause of the asymmetry in the research lies preliminary in a aesthetic valuation of the text that is insufficient to the claims of the speaker, which is decisive for the failure of the discursive catchment strategy, which, by the inadequacy of the speaker placement in relation to the alocutary, failed to lead him into the "universe of thought" of the speaker to share its "intentionality, emotion and values," thus leading to the failure of the enunciative alocutive organization mode, which sought to influence the alocutary to assume a certain behavior, in the case of stand-up comedy on the purpose of "making laugh" (according to the incitative offeree of "make believe"), due to the transfer of rejection observed in relation to the subject enunciator (Ie) for communicating the subject (Ic) (transfer effects between the internal and external circuits)